2021
DOI: 10.1002/ps.6529
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive insights into host‐pathogen interaction between brown planthopper and a fungal entomopathogen by dual RNA sequencing

Abstract: BACKGROUND The brown planthopper (BPH) is one of the most destructive pests of rice, causing tremendous yield and economic losses every year. The fungal entomopathogen Metarhizium anisopliae was previously proved to have great potential for BPH biocontrol. Genome‐wide insight into the insect‐fungus interaction is crucial for genetic improvement of M. anisopliae to enhance its virulence to BPH but still has been poorly explored. RESULTS Using dual RNA‐seq approach, we present here a global view of host and fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 56 publications
2
7
1
4
Order By: Relevance
“…Aerial conidia of Ma456 produced on PDA plates were washed with 0.02% Tween 80 solution and adjusted to a final concentration of 1 × 10 8 conidia/mL using a hemocytometer. BPH nymphs (24 h after molting at the fifth instar) were prepared for topical fungal infection following previous protocol [ 14 ]. Briefly, batches of 30–40 nymphs on 3-cm high rice seedlings in uncaged cups were sprayed with 1 mL conidial suspension using a handheld micro sprayer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aerial conidia of Ma456 produced on PDA plates were washed with 0.02% Tween 80 solution and adjusted to a final concentration of 1 × 10 8 conidia/mL using a hemocytometer. BPH nymphs (24 h after molting at the fifth instar) were prepared for topical fungal infection following previous protocol [ 14 ]. Briefly, batches of 30–40 nymphs on 3-cm high rice seedlings in uncaged cups were sprayed with 1 mL conidial suspension using a handheld micro sprayer.…”
Section: Methodsmentioning
confidence: 99%
“…In the insects–fungi interaction model, immune aspects in insects have been extensively studied in individuals or tissues (hemolymph and fat body) that are traditionally attributed to immune responses [ 10 , 11 , 12 ]. A large number of immune-related genes have been found to be up-regulated in the whole BPH body after topical infection with M. anisopliae based on comparative transcriptomic analysis [ 13 , 14 ]. Nowadays, accumulating studies have revealed that the gut also plays an important role in shaping insect immunity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El metabolismo de las proteínas fúngicas (tanto las rutas anabólicas como las catabólicas) también se encontró aumentado, lo que indica que existe una alta tasa de intercambio de proteínas. Estos hallazgos coinciden con los encontrados por Wang et al (2021) y puede estar relacionado con el hecho de que el patógeno se está adaptando para invadir al huésped y, por lo tanto, necesita redirigir su maquinaria proteica hacia el proceso infectivo. Además, los procesos redox y la respuesta al estrés mostraron altos niveles de expresión, lo que sugiere que el patógeno fúngico está tratando de superar las barreras del sistema de defensa inmune de T. castaneum.…”
Section: Perfiles De Expresión Génica En La Interacción Beauveria Bas...unclassified
“…Recientemente, Wang et al (2021) realizaron un estudio de RNA-seq dual en Nilaparvata lugens asperjados con una suspensión de conidios de M. anisopliae. Estos autores informaron que 2.773 y 3.895 genes fúngicos se expresaron en los adultos infectados con hongos a las 48 hs y 72 hs después del tratamiento, respectivamente, lo que representa aproximadamente el 0,01 % del total de lecturas encontradas.…”
Section: Perfiles De Expresión Génica En La Interacción Beauveria Bas...unclassified